2020
DOI: 10.3762/bjoc.16.6
|View full text |Cite
|
Sign up to set email alerts
|

Light-controllable dithienylethene-modified cyclic peptides: photoswitching the in vivo toxicity in zebrafish embryos

Abstract: This study evaluates the embryotoxicity of dithienylethene-modified peptides upon photoswitching, using 19 analogues based on the β-hairpin scaffold of the natural membranolytic peptide gramicidin S. We established an in vivo assay in two variations (with ex vivo and in situ photoisomerization), using larvae of the model organism Danio rerio, and determined the toxicities of the peptides in terms of 50% lethal doses (LD 50 ). This study allowed us to: (i) demonstrate the feasibility of evaluating peptide toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Before photoresponsive molecules can enter clinical trials and be used in medical applications, it is necessary to perform in vivo toxicity studies. 88 The extent of these toxicity studies will depend on the target amount to be injected. E.g.…”
Section: Toxicitymentioning
confidence: 99%
“…Before photoresponsive molecules can enter clinical trials and be used in medical applications, it is necessary to perform in vivo toxicity studies. 88 The extent of these toxicity studies will depend on the target amount to be injected. E.g.…”
Section: Toxicitymentioning
confidence: 99%
“…Although there is growing concern about the use of animal models to predict human drug toxicity [16], numerous studies have revealed that rodent and nonrodent safety data are sufficiently predictive of the extent and type of adverse effects that could be experienced in subsequent human clinical trials [17][18][19], provided that the methodology of the preclinical safety data acquisition was correct [20]. Surprisingly, literature reports on the toxicity of photocontrollable biologically active compounds in multicellular organisms are very scarce, with most simply using lower vertebrates, such as zebrafish embryos, as their test subjects [21][22][23][24][25]. To the best of our knowledge, toxicity data on different photoforms of photoswitch-modified compounds have never been determined and compared in mammals [25][26][27][28].…”
mentioning
confidence: 99%
“…Indeed, very few systemic in vivo applications of photopharmaceuticals have been made. As none of those have tested a defined mechanism of drug action, nor explored the optical-scale spatiotemporally-resolved targeting which is the only benefit of photopharmaceutical approaches as compared to conventional drugs, [53][54][55] the ability of photopharmacology to contribute useful systemically-applicable reagents for organism studies has remained unclear.…”
Section: Discussionmentioning
confidence: 99%